In situ dry matter and nitrogen degradability of ammonium nitrate and urea treated dry veld grass and Zea mays stover in mature goats - Chivandi, E.; Chipfupa, L. (Livestock Research for Rural Development, 2021)
An in situ degradability study, in a factorial randomised complete block design, was carried out using three rumen-cannulated Kapaters (mature male castrate goats) to investigate the effects of ammonium nitrate treatment on poor quality roughages. The study was carried out in two phases: phase 1 had dry veld grass subjected to ammonium nitrate and urea treatment and phase 2 had maize stover similarly treated. Phase 1 treatments were: untreated dry veld grass only (DVG, control), urea treated dry veld grass (UDVG) and ammonium nitrate treated dry veld grass (ANDVG). Phase 2 treatments were made up of untreated maize stover (MS, control), urea treated maize stover (UMS) and ammonium nitrate treated maize stover (ANMS).